2005
DOI: 10.1111/j.1551-2916.2005.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics on a Second Scale at Temperatures up to 2300 K—The Reduction of Manganese Oxide in a Solar Furnace

Abstract: Testing the chemical stability of high‐performance ceramics at temperatures above 1800 K is a demanding task. With the aim to provide an experimental set‐up for kinetic studies on gas releasing reactions at temperatures up to 2300 K, a solar reactor has been interfaced to a mass spectrometer. Tracer experiments revealed that the reactor behaves as a continuous ideally stirred tank. This characteristic provides a straightforward path to extract kinetic data for such reactions from gas‐phase analysis. The approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The outlet was fitted with a cooling mechanism. Using results from an earlier investigation of flow patterns by Frey et al [37] which demonstrated that the entire apparatus behaved like an optimally stirred continuous tank, online gas measurement at the outlet could readily calculate gas release rates. To decrease iron and manganese oxides, TREMPER was utilized, with 25 percent of the iron oxide and 85 percent of the manganese oxide attaining their maximal chemical conversion rate.…”
Section: Fixed-configuration Reactorsmentioning
confidence: 99%
“…The outlet was fitted with a cooling mechanism. Using results from an earlier investigation of flow patterns by Frey et al [37] which demonstrated that the entire apparatus behaved like an optimally stirred continuous tank, online gas measurement at the outlet could readily calculate gas release rates. To decrease iron and manganese oxides, TREMPER was utilized, with 25 percent of the iron oxide and 85 percent of the manganese oxide attaining their maximal chemical conversion rate.…”
Section: Fixed-configuration Reactorsmentioning
confidence: 99%
“…A quenching unit was included at the outlet. A flow patterns analysis determined the whole apparatus behaved as a continuous ideally stirred tank [47] and hence, gas release rates could conveniently be obtained from on-line gas analysis at the outlet. Reduction of iron and manganese oxides were performed at TREMPER and maximal chemical conversion reached was 25% for iron oxide and 85% for manganese oxide.…”
Section: Fixed Reactorsmentioning
confidence: 99%